The Influence of Basic Literacy on the Reading Ability of Class IV Students of SDN 065011 Medan Selayang District School - Anita; Lumbanraja, Bogor; Sitepu, Anton; Remigius Abi, Antonius; Sofia Tanjung, Darinda; Janson Silaban, Patri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This research aims to determine the effect of basic literacy on the reading ability of fourth grade students at SD Negeri 065011 Medan Selayang, district for the 2023/2024 academic year. This type of research is quantitative using the expost-facto method. The population of this study was all fourth grade students at SD Negeri 065011 Medan Selayang District, totaling 77 students. Sampling was taken using a purposive sampling technique and 28 students were obtained. The results of this study show that students' reading ability is in the very good category with an average of 82.46. The results of this research show that the results of the correlation test can be seen that the correlation coefficient is 0.687, meaning that r_count (0,687) ≥ r_tabel (0.374) then is accepted. So there is a very strong influence between basic literacy on the reading ability of students in class IV of SD Negeri 065011 Medan Selayang District. It can also be seen from the t-test where t_count > t_table, namely 4,817 ≥ 2,056, thus stating that h_a is accepted. This shows that there is a significant positive influence from the use of basic literacy on the reading ability of students in class IV of SD Negeri 065011, Medan Selayang District, Academic Year 2023/2024.